EVALUASI PROGRAM BIMBINGAN DAN KONSELING BERBASIS CIPP PADA MASA PANDEMI COVID-19 - Utomo, Setyo Budi; Atma, Elisabet Setia; Dwikurnaningsih, Yari; Loekmono, J.T Lobby (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2023)
The purpose of evaluating the Guidance and Counseling (BK) program at SMP Negeri 2 Ambarawa during the pandemic is to evaluate the context, input, process and product of the guidance and counseling program during the pandemic. This research is evaluative research. The principal provides full support in implementing counseling services during the pandemic by providing a schedule and budget allocation. The ratio of counseling teachers to students is fulfilled by the presence of school counselors with a background in counseling education. Facilities and infrastructure are in good condition, but do not yet have a special counseling room. BK services are carried out with the help of applications, namely Google classroom, and google forms used by school counselors for delivery systems in service activities with asynchronous types and in synchronous types using WhatsApp, Zoom or Google Meet depending on the agreement between teachers and students. The problems experienced in the implementation of online counseling services are less than optimal since not all students have devices. The essential material compiled by the MGBK is less appropriate to use, it is more appropriate to use a needs assessment of students to develop a BK program. School counselors provide time for learners to consult with flexible time, either through in-person or device-assisted.